Students' Writing Motivation of the Third Semester Students OF STIBA Persada Bunda - barruansyah, rauf Tetuko (J-SHMIC : Journal of English for Academic, 2019)
Abstract             Motivation is one of the keys of success in learning because motivation is a factor that encourages the learners taking action and being active in learning process. In the study of Kinder in Washoe, he found that motivation is psychological mechanisms governing the direction, intensity, and persistence of action not due to solely to individual difference in ability to overwhelming environmental demands that coerce the force action. Sometimes, motivation can become a problem when it was low. So, the learners need to increase their writing motivation by doing some interesting activities. The goal of this research was to know how far students’ writing motivation. The subject of this research was the fourth semester students of Sekolah Tinggi Ilmu Bahasa Asing (STIBA) Persada Bunda, and the object was the students’ writing motivation. The writer used simple sampling to take the sample. Based on the data analysis, The percentage of students’ writing motivation score was 77.48%. It can concluded that students’ writing motivation of the third semester students of Persada Bunda was in Strong Level.    Keywords: Students’ writing motivation, Writing   MOTIVASI MENULIS MAHASISWA PADA MAHASISWA SEMESTER 3 SEKOLAH TINGGI ILMU BAHASA ASING PERSADA BUNDA   Abstrak             Motivasi adalah salah satu kunci kesuksesan didalam belajar karena motivasi adalah factor yang mendorong peserta didik untuk beraksi dan aktif didalam proses pembelajaran. Didalam penelitian oleh Kinder, dia menemukan bahwa mativasi adalah mekanisme perintah secara psikologi, intensitas, dan ketekunan dalam beraksi tidak semata mata karena perbedaan kemampuan untuk memeunhi permintaan lingkungan yang memaksa untuk melakukan aksi. Terkadang, motivasi bisa menjadi sebuah masalah ketika ia rendah. Jadi, mahasiswa perlu untuk meningkatkan motivasi menulis mereka dengan melakukan beberapa aktifitas yang menarik. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana tingkat motivasi menulis mahasiswa. Suyek penelitian ini adalah mahasiswa semester 3 Sekolah Tinggi Ilmu Bahasa Asing Persada Bunda, dan obyek penelitiannya adalah Motivasi menulis mahasiswa. Penulis menggunakan Simple sampling untuk mengambil sampel. Berdasarkan analisis data, persentase dari motivasi menulis mahasiswa berada pada nilai 77.48%. Hal ini dapat disimpulkan bahwa motivasi menulis mahasiswa semester 3 STIBA Persada Bunda adalah pada level “kuat”.   Kata-kata kunci: Motivasi Menulis, Menulis.